Intra-seasonal oscfffations of radio refractive index during southwest monsoon over India - SRIVASTAVA, H. N.; SINHARAY , K. C.; MUKHOPADHYAY, R. K. (MAUSAM, 1993)
The study deals with the spatial and temporal variations of intra-seasonal oscillations in radio refractive index during southwest monsoon season over India and islands over Indian seas. Average daily radio refractive index data from 1 June to 30 September and that of the individual years for the period 1969-1986 were subjected to harmonic analysis to investigate the contributions of various periodicities in monsoon radio refractive index. The inter-annual variability of various intra-seasonal oscillations have been studied for each 5° latitudinal strip from 50 oN to 30° N with the help of variance explained by various frequency modes for different years. Variance explained by 30-60 day and 10-20 day modes were studied in relation to monsoon performance. The northward and eastward propagation of30.60 day mod was noticed. The 10.20 day mode and seasonal mode dominate at latitudinal belts 5°N.10oN and 25°N-30°N respectively. Between 10°N and 25°N, both 30-60 day and 10-20 day modes occur.